Understanding impulse buying in mobile commerce: An investigation into hedonic and utilitarian browsing. (October 2019) - Zheng, Xiabing; Men, Jinqi; Yang, Feng; Gong, Xiuyuan
Highlights: Portability, visual appeal and interpersonal influence are key situation factors affecting consumers' urge to buy impulsively. Hedonic browsing has a significant influence on consumers' urge to buy impulsively. Utilitarian browsing has an indirect influence on urge to buy impulsively via hedonic browsing. Abstract: Growing evidence shows that mobile commerce will increase consumers' impulse buying behavior. However, existing study examining the impact factors on individuals' impulse buying in mobile commerce is limited. Drawing on stimulus-organism-response (S-O-R) paradigm, this study focuses on situation factors and reaction factors in mobile commerce to examine impulse buying. Building on prior literature of browsing and motivation theory, this study views hedonic browsing and utilitarian browsing as two key drivers on impulse buying in mobile commerce. This study adopts partial least squares estimation to analyze the data obtained from an online questionnaire. Two main findings emerge. First, three situation factors (portability, visual appeal and interpersonal influence) differently affect hedonic browsing and utilitarian browsing. Second, hedonic browsing directly and positively influences consumers' urge to buy impulsively, whereas utilitarian browsing indirectly influences consumers' urge to buy impulsively through hedonic browsing. Discussions, limitations, and implications are also presented in the paper.